A life cycle assessment model for evaluating the environmental impacts of building construction in Hong Kong. (July 2015) - Dong, Ya Hong; Ng, S. Thomas
Abstract: Building construction consumes large amount of energy and material. Despite that, not much effort has been directed to examine the environmental impact of the construction phase, and this is particularly relevant to Hong Kong where the demand for building construction is ever increasing. In this study, a life cycle assessment (LCA) model namely the Environmental Model of Construction (EMoC) is developed to help decision-makers assess the environmental performance of building construction projects in Hong Kong from cradle to end of construction. The model provides comprehensive analyses of 18 environmental impact categories at the midpoint and endpoint levels. By inputting project specific data to EMoC, it can generate results of over two-hundred detailed processes. A public rental housing (PRH) project is fed into EMoC to examine the environmental performance of this type of projects. The results indicate that material is the major contributor to environmental impacts of the upstream stages of public housing construction. The carbon emissions of the studied project amount to 637 kg carbon dioxide equivalent per square meter of the gross floor area. Sensitivity analysis reveals that the environmental pollution can be significantly reduced by adopting a higher proportion of precast concrete components. The model should help support decision-makers identifying pragmatic solutions to reduce the environmental burden of a building project at the design, procurement and construction stages. Highlights: EMoC is developed to evaluate the environmental impacts of building construction. Carbon emissions of the PRH project account for 637 kg CO2 e per m 2 of GFA. Adoption of precast concrete can significantly reduce the environmental pollution.